Atividade alelopática em folhas de Tachigali myrmecophyla (Leg. - Pap.) - SOUZA FILHO, Antonio Pedro da Silva (2014)
The use of forest species with allelopathic activity can promote a higher stability to agroforestry systems, mainly relative to the reduction of weed species. The objective of this study was to isolate and identify chemical substances produced by Tachigali myrmecophyla and characterize its inhibitory allelopathic activity on the germination and seedling development of two weed species. Bioassays were carried out under controlled conditions of 25 ºC and 12-hour photoperiod for germination and 24-hour photoperiod for radicle and hypocotyl development. The extracts and fractions were analyzed under concentrations of 1.0% and 0.5%, and the substance under concentrations of 5, 10, 15 and 20 ppm. The isolation process allowed the identification of the chemical substance 4,5-dihydroblumenol A. This substance showed allelopathic activity, with the effects varying according to concentration, weed species and the plant parameter analyzed. The intensity of the allelopathic effects was positively associated to the concentration. Mimosa pudica was the most affected weed species. Radicle development was more sensitive plant to the substance effects than hypocotyl development and seedling germination.